Age and exercise: a theoretical and empirical analysis of the effect of age and generation on physical activity - Klein, Thomas; Becker, Simone (Journal of public health, 2012)
The well-documented association of reductions in physical activity with age is based largely on cross-sectional studies that do not distinguish between prevalence of physical activity and initiation/discontinuation patterns. These studies also fail to consider the changes in physical activity as a function of life stage. We investigated how physical activity evolves over a lifetime. We distinguished between prevalence and initiation/discontinuation patterns and also considered multidirectional age effects.
Published online: 17 May 2011
Gesehen am 19.04.2023